Converting paved roads to unpaved (Synthesis of highway practice, 2016)
"TRB National Cooperative Highway Research Program (NCHRP) Synthesis 485: Converting Paved Roads to Unpaved explores how common and under what conditions paved roads are converted to unpaved. NCHRP Synthesis 485 found that the practice of converting paved roads to unpaved is relatively widespread; recent road conversion projects were identified in 27 states. These are primarily rural, low-volume roads that were paved when asphalt and construction prices were low. Those asphalt roads have now aged well beyond their design service life, are rapidly deteriorating, and are both difficult and expensive to maintain. Instead, many local road agencies are converting these deteriorated paved roads to unpaved as a more sustainable solution. According to the report, local road agencies have experienced positive outcomes by converting roads. Many local road agencies reported cost savings after converting, compared with the costs of continuing maintenance of the deteriorating paved road, or repaving. One key to successful conversion is early involvement of the public in the planning process. Other techniques that can be used to improve the overall results of a project include treating or stabilizing granular surfaces to control dust, limiting the rate of aggregate loss, and reducing motor grader/blade maintenance frequency. Stabilization procedures can also improve safety, increase public acceptance, and reduce life-cycle costs and environmental impacts after a conversion has taken place."--Publisher's description.